Предмет: Алгебра,
автор: apmep16
Помогите пожалуйста,только по быстрее,заранее Спасибо
a)(d-1)(3+d)-(d-2)²=
б)5(x+y)²-10xy=
в)(z+3)(z²-3z+9)-z³=
Ответы
Автор ответа:
0
А) (d-1)(3+d)-(d-2)²=3d+d²-3-d-d²+4d-4=6d-7
б) 5(x+y)²-10xy=5x²+10xy+5y²-10xy=5(x²+y²)
в) (z+3)(z²-3z+9)-z²=z³+27-z²
б) 5(x+y)²-10xy=5x²+10xy+5y²-10xy=5(x²+y²)
в) (z+3)(z²-3z+9)-z²=z³+27-z²
Автор ответа:
0
это а)
(d-1)(3+d)-(d-2)^2
3d+d^2-3-d-(d^2-4d+4)
3d+d^2-3-d-d^2+4d-4
3d-(3+4)-1d+4d
(3-1+4)d-7
6d-7
(d-1)(3+d)-(d-2)^2
3d+d^2-3-d-(d^2-4d+4)
3d+d^2-3-d-d^2+4d-4
3d-(3+4)-1d+4d
(3-1+4)d-7
6d-7
Похожие вопросы
Предмет: Английский язык,
автор: asemgul16120417
Предмет: Алгебра,
автор: lovegdsshhsjzhshz
Предмет: Русский язык,
автор: alisaplatoskina
Предмет: Математика,
автор: ксенияходжибоева619